Assessing the measurement invariance of two positive body image instruments in adults from Malaysia and the United Kingdom. (September 2020) - Todd, Jennifer; Swami, Viren
Highlights: Body Appreciation Scale-2 scores are partially invariant across UK and Malay adults. Functionality Appreciation Scale scores are partially invariant across UK and Malay adults. Malaysian participants have significantly greater positive body image than UK participants. Men have significantly greater positive body image than women in the UK. Women have significantly greater positive body image than men in Malaysia. Abstract: Despite the growth of positive body image research in recent years, our understanding of the construct across different national contexts remains limited. Here, we investigated measurement invariance of the Body Appreciation Scale-2 (BAS-2) and the Functionality Appreciation Scale (FAS) across ethnically homogenous groups of adults from Malaysia ( n = 815, women n = 403) and the United Kingdom (UK; n = 596, women n = 416). Using multi-group confirmatory factor analysis, partial scalar invariance was supported for scores on both measures after fixing the intercepts for BAS-2 Items 6 and 8, and FAS Item 4. Next, we examined differences in latent scores across nationality and gender. The results of an analysis of covariance (with age and body mass index as covariates) indicated a significant nationality by gender interaction: Malaysian women had higher scores than Malaysian men on both the BAS-2 and FAS, but UK men had higher scores than UK women. There were also significant main effects of nationality (Malaysian participants had significantly higher body appreciation and functionality appreciation than UK participants) and gender (men had significantly higher body appreciation than women). These findings are discussed in terms of cross-national and gendered understandings of positive body image.